Condición nutricional en la puna argentina - Moreno Romero, Susana; Lomaglio, Delia B.; Jail Colome, José; Alba, Joisé A.; Lejtman, Néstor; Dipierri, José E.; Marrodan, M.ª Dolores (Observatorio Medioambiental, 2005)
The purpose of the present study is to assess the nutritional status of two populations of the Argentinean Puna that hold different socioeconomic conditions: Susques (Jujuy province) and Antofagasta de la Sierra (Catamarca province). The sample consisted of 491 children aged 5 to 18 years old. It was measured weight, height and body mass index (BMI). The weight/age, height/age and BMI/age indexes were estimated and compared with the Frisancho´s (1990) and Cole´s et al. (2000) standard growth tables. Most of the subjects fell below the 50th percentile. The results of the direct anthropometric measurement showed high frequencies of underweight and stunting amongst both populations. Lower percentages of underweight and stunting were obtained when comparing the BMI. Boys and girls of Susques have a better nutritional condition than those from Antofagasta. These results could be explained for disparities in the socioeconomic conditions of both communities.